Biotechnological Combination for Co-contaminated Soil Remediation: Focus on Tripartite “Meta-Enzymatic” Activity - Tartaglia, Maria; Zuzolo, Daniela; Postiglione, Alessia; Prigioniero, Antonello; Scarano, Pierpaolo; Sciarrillo, Rosaria; Guarino, Carmine (Frontiers in Plant Science, 2022)
Soil pollution is a pressing problem requiring solutions that can be applied without large-scale side effects directly in the field. Phytoremediation is an effective strategy combining plant and root-associated microbiome to immobilize, degrade and adsorb pollutants from the soil. To improve phytoremediation, it is necessary to think of plants, fungi and bacteria not as individual entities, but as a meta-organism that reacts organically, synergistically and cooperatively to environmental stimuli. Analysing the tripartite enzymatic activity in the rhizosphere is necessary to understand the mechanisms underlying plant-microorganism communication under abiotic stress (such as soil pollution). In this work, the potential of a microbial consortium along with a plant already known for its phytoremediation capabilities, Schedonorus arundinaceus (Scheb.) Dumort., was validated in a mesocosm experiment with pluricontaminated soil (heavy metals, PAHs and PCBs). Chemical analyses of the soil at the beginning and end of the experiment confirmed the reduction of the main pollutants. The microscopic observation and chemical analyses confirmed the greater root colonization and pollutant removal following the microbial treatment. To obtain a taxonomic and functional picture, tripartite (plant, fungi and bacteria) enzyme activity was assessed using a metatranscriptomic approach. Total RNA was extracted from a sample of rhizosphere sampled considering 2 centimetres of root and soil attached. From the total reads obtained, mRNAs were filtered, and analysis focused on reads identified as proteins with enzymatic activity. The differential analysis of transcripts identified as enzymes showed that a general increase in potential enzyme activity was observed in the rhizosphere after our biotechnological treatment. Also from a taxonomic perspective, an increase in the activity of some phyla, such as Actinobacteria and Basidiomycota was found in the treated sample compared to the control. An increased abundance of enzymes involved in rhizospheric activities and pollutant removal (such as dehydrogenase, urease, laccase etc.) was found in the treated sample compared to the control at the end of the experiment. Several enzymes expressed by the plant confirmed the increase in metabolic activity and architectural rearrangement of the root following the enhancement of the rhizospheric biome. The study provides new outcomes useful in rhizosphere engineering advancement.